Effect on wheat (Triticum aestivum) yield of the yellow rust caused by Puccinia striiformis f. sp. tritici and its effect on yield - Lavilla, Miguel (2021)
Introduction. In recent years, yellow rust caused by Puccinia striiformis was the most prevalent disease in wheat (Triticum aestivum), in the north of the province of Buenos Aires, Argentina. Objective. To evaluate the progress of yellow rust in wheat cultivars, with and without foliar fungicide application and its effect on yield and its components. Materials and methods. This study was carried out during two consecutive years (2017 and 2018) in the town of Junín, Buenos Aires, Argentina, on nineteen wheat cultivars, with and without foliar fungicide application. The damages of yellow rust on yield and industrial quality were quantified. Likewise, the evolution of the disease was evaluated using the area under the disease intensity progress curve (ABCPIE). The ABCPIE was associated with the yield, its components, and hectoliter weight. Results. Of all the variables analyzed, the ABCPIE had a significant interaction (p<0.05) between the foliar fungicide application and the cultivar used. The cultivars Lapacho, Minerva, MS 415, and SY 211 were resistant to yellow rust. The cultivar most susceptible to the disease was Algarrobo. The application of foliar fungicide, with low levels of the disease, significantly reduced its evolution, as reflected from the area under the disease intensity progress curve. Conclusion. The evolution over time of the yellow rust caused by P. striiformis depended on the genetic behavior of the cultivar and the application of foliar fungicide. The cultivars that had the highest yields, lowest ABCPIE, and highest hectoliter weight were: Lapacho, SY 11, BIO 1006, and Minerva.